O teatro do oprimido como instrumento para a educação ambiental - Silva, Flávio José Rocha da (2010)
This research focuses on the Theater of the Oppressed as a tool for Environmental Education. Although the initial motivation of this theater technique was to discuss the oppressive relationships between human beings, our work had the intention to understand how this methodology can be undertaken with a group of students in a public school to talk about the environmental crisis. Our research was made with a group of volunteer students from the Professor Antônio Gomes Middle and High School, located in the neighborhood of Mutirão-Bayuex/PB during the second semester of 2008 and the first semester of 2009. Throughout this time, we coordinated thirty workshops on the Theater of the Oppressed techniques and discussed themes connected to the environment on each acti vity. At the end of each semester , the group presented a play focusing on the garbage on the school grounds and class rooms and on the devastati on the Mata do Xém-xém State Park, located in the same neighborhood. At the beginning of our research and at the end of our workshops, we applied questionnaires with the Eighth, Ninth, Eleventh and Twelfth grade students to discover if there was an increase in the level of understanding of environmental problems and concepts like nature, environment and environmental education. Our research confirms that the Theater of the Oppressed can be a tool to facilitate a critical Environmental Education and promote Environmental Justice in a participatory method.